A UML profile for documenting the component-and-connector view of software architectures - Anacleto, Valerio Adrián (2008)
In this paper, we present a UML profile and a group of UML patterns for documenting the component-andconnector views of software architectures [8]. They facilitate the creation of the component and connector viewtype in any UML 2.0 tool with a compliance level 3 [14]. This work's contributions are: (1) Facilitating the documentation of all the software application's views using only one tool. (2) Curtailing investment in personnel training. (3) Allowing the establishment of an adequate traceability between the architectural artifacts and the rest of the model.